2021
DOI: 10.3390/vaccines9010042
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of COVID-19 Vaccine Hesitancy and Its Association with Conspiracy Beliefs: A Study in Jordan and Kuwait among Other Arab Countries

Abstract: Vaccination could be an effective strategy for slowing the spread of the current coronavirus disease 2019 (COVID-19) pandemic. Vaccine hesitancy could pose a serious problem for COVID-19 prevention, due to the spread of misinformation surrounding the ongoing pandemic. The aim of this study was to assess the attitudes towards the prospective COVID-19 vaccines among the general public in Jordan, Kuwait and other Arab countries. We also aimed to assess the association between COVID-19 vaccine acceptance and consp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

77
654
21
22

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 575 publications
(774 citation statements)
references
References 83 publications
77
654
21
22
Order By: Relevance
“…In the USA, an estimated 86% of people over 61 years of age are more likely to receive the vaccine against SARS-CoV-2 [28]. Another study in Jordan and Kuwait found that the SARS-CoV-2 vaccine acceptance rate is higher among males and people with higher educational attainment [29]. Surprisingly, our study suggests that, compared to Dhaka city residents, residents of other cities are significantly less likely to have a definite intent against vaccination.…”
Section: Discussioncontrasting
confidence: 77%
“…In the USA, an estimated 86% of people over 61 years of age are more likely to receive the vaccine against SARS-CoV-2 [28]. Another study in Jordan and Kuwait found that the SARS-CoV-2 vaccine acceptance rate is higher among males and people with higher educational attainment [29]. Surprisingly, our study suggests that, compared to Dhaka city residents, residents of other cities are significantly less likely to have a definite intent against vaccination.…”
Section: Discussioncontrasting
confidence: 77%
“…A total of 178 records were identified, and following the screening process, a total of 30 articles were included in this review (Figure 1). In addition, data collected in a recently published article that surveyed the general public residing in Jordan and Kuwait were added to the final analysis [45].…”
Section: Resultsmentioning
confidence: 99%
“…The Middle East was among the regions with the lowest COVID-19 vaccine acceptance rates globally. The acceptance rate was the lowest in Kuwait (23.6%), followed by Jordan (28.4%), Saudi Arabia (64.7%) and Turkey (66.0%) [45,62,75]. Such low rates can be related to the widespread embrace of conspiratorial beliefs in the region, with its subsequent negative attitude towards vaccination [23,[99][100][101].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Third, the MoVac-COVID19S can be used to explore and understand why a population reports lower levels of motivation to get vaccinated. Although many studies have reported the high willingness of COVID-19 vaccinating uptake [e.g., 21,[35][36][37][38], low acceptance can still be observed [39][40][41]. Therefore, with the use of MoVac-COVID19S, healthcare providers and researchers can obtain in-depth information regarding the underlying mechanism of individuals who are unwilling to get vaccinated.…”
Section: Discussionmentioning
confidence: 99%